Access to mental health services and psychotropic drug use in refugees and asylum seekers hosted in high-income countries. (October 2015) - Nosè, M.; Turrini, G.; Barbui, C.
<x content-type="archive" xml:space="preserve">Abstract</x> In the populations of refugees and asylum seekers hosted in high-income countries, access to mental health care and psychotropic drugs, is a major challenge. A recent Swedish cross-sectional register study has explored this phenomenon in a national cohort of 43 403 young refugees and their families from Iraq, Iran, Eritrea, Ethiopia, Somalia and Afghanistan. This register study found lower rates of dispensed psychotropic drugs among recently settled refugees, as compared with Swedish-born residents, with an increase in the use with duration of residence. In this commentary, the results of this survey are discussed in view of their global policy implications for high-income countries hosting populations of refugees and asylum seekers.